2015
DOI: 10.1523/jneurosci.4672-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin+ Neurons and Npas1+ Neurons Are Distinct Neuron Classes in the Mouse External Globus Pallidus

Abstract: Compelling evidence suggests that pathological activity of the external globus pallidus (GPe), a nucleus in the basal ganglia, contributes to the motor symptoms of a variety of movement disorders such as Parkinson's disease. Recent studies have challenged the idea that the GPe comprises a single, homogenous population of neurons that serves as a simple relay in the indirect pathway. However, we still lack a full understanding of the diversity of the neurons that make up the GPe. Specifically, a more precise cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
297
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(339 citation statements)
references
References 136 publications
39
297
1
Order By: Relevance
“…We found that the SSRT can be effectively modulated by some specific intrinsic BG connections, in particular the newly discovered pathway from the external segment of the globus pallidus (GPe) to the striatum (Abdi et al, 2015; Dodson et al, 2015; Hegeman et al, 2016; Hernandez et al, 2015; Mallet et al, 2012) plays an essential role in cancelling a planned response in midcourse, in support of the recent physiological report (Mallet et al, 2016). The thalamocortical connection exerts a two-level modulation of SSRT by switching the distributed attractor network between states with or without persistent activity.…”
Section: Introductionsupporting
confidence: 82%
“…We found that the SSRT can be effectively modulated by some specific intrinsic BG connections, in particular the newly discovered pathway from the external segment of the globus pallidus (GPe) to the striatum (Abdi et al, 2015; Dodson et al, 2015; Hegeman et al, 2016; Hernandez et al, 2015; Mallet et al, 2012) plays an essential role in cancelling a planned response in midcourse, in support of the recent physiological report (Mallet et al, 2016). The thalamocortical connection exerts a two-level modulation of SSRT by switching the distributed attractor network between states with or without persistent activity.…”
Section: Introductionsupporting
confidence: 82%
“…Subsequently, we detected each probe using the TSA system in series. As shown in Figure 7, miR-34a signals were co-localized with PV signals in the TRN, the globus pallidus and the entopeduncular nucleus, where GABAergic neurons are localized (Hernández et al, 2015). ISH using the sense probe of PV mRNA did not detect any ISH signals (data not shown).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…This process could be important for encoding functional segregation of movements within the GPe (Hegeman et al, 2016; Jin et al, 2014; Shi et al, 2004; Turner and Anderson, 2005). The pathophysiology of PD can be explained by the changes in the activity levels and synchrony in the GPe (Bergman et al, 1998; Chan et al, 2011; Hegeman et al, 2016; Hernandez et al, 2015; Kita and Kita, 2011). In a normal state, individual GPe neurons respond specifically to the movement in one direction of a single joint on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%